Interpretation of the Observed Neutrino Emission from Three Tidal Disruption Events - Walter Winter; Cecilia Lunardini (The Astrophysical Journal, 2023)
Three Tidal Disruption Event candidates (AT2019 dsg , AT2019 fdr , and AT2019 aalc ) have been associated with high-energy astrophysical neutrinos in multimessenger follow-ups. In all cases, the neutrino observation occurred ${ \mathcal O }(100)$ days after the maximum of the optical-ultraviolet (OUV) luminosity. We discuss unified fully time-dependent interpretations of the neutrino signals where the neutrino delays are not a statistical effect, but rather the consequence of a physical scale of the post-disruption system. Noting that X-ray flares and infrared (IR) dust echoes have been observed in all cases, we consider three models in which quasi-isotropic neutrino emission is due to the interactions of accelerated protons of moderate, medium, and ultra-high energies with X-rays, OUV, and IR photons, respectively. We find that the neutrino time delays can be well described in the X-ray model assuming magnetic confinement of protons in a calorimetric approach if the unobscured X-ray luminosity is roughly constant over time, and in the IR model, where the delay is directly correlated with the time evolution of the echo luminosity (for which a model is developed here). The OUV model exhibits the highest neutrino production efficiency. In all three models, the highest neutrino fluence is predicted for AT2019 aalc , due to its high estimated supermassive black hole mass and low redshift. All models result in diffuse neutrino fluxes that are consistent with observations.